1996
DOI: 10.1021/ja953091m
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemistry:  Molecular Dynamics Study of the Dark-Adaptation Process in Bacteriorhodopsin

Abstract: Molecular dynamics simulations and quantum chemistry calculations have been combined to describe the dark adaptation in bacteriorhodopsin (bR). The process involves the reversible thermally activated transformation of retinal from an all-trans to a 13-cis,15-syn configuration. The potential surface governing the thermal isomerization of retinal around two (13−14, 15−N) double bonds has been determined for representative protein configurations taken from molecular dynamics trajectories. CASSCF(8,8)/6-31G level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 75 publications
3
50
0
Order By: Relevance
“…They reflect the changes due to the vibrationally hot dynamics in the ground state after the initial product assignment was made. This is also manifested by the large number of structures that could not be assigned to one of the types of (20) 25 (25) torsional motion at the end of the dynamics since at least one of the dihedral angles was located between 60 and 120°, that is, far away from planarity. Because of the large number of undetermined motions it is difficult to distinguish trends in the product formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reflect the changes due to the vibrationally hot dynamics in the ground state after the initial product assignment was made. This is also manifested by the large number of structures that could not be assigned to one of the types of (20) 25 (25) torsional motion at the end of the dynamics since at least one of the dihedral angles was located between 60 and 120°, that is, far away from planarity. Because of the large number of undetermined motions it is difficult to distinguish trends in the product formation.…”
Section: Resultsmentioning
confidence: 99%
“…These photoisomerization processes 8,9 belong to the fastest photochemical reactions in nature 1 and have been studied extensively in experimental [10][11][12][13] and theoretical investigations. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The large size of RPSB and the multireference character of the electronic wave function make high level accurate calculations very difficult to perform, especially when dynamics simulations are intended. Because of this limitation, the photochemical properties of RPSB have been studied theoretically mostly by simulation of model systems.…”
Section: Introductionmentioning
confidence: 99%
“…Given this centrality of function, the accessibility switch has been extensively explored in structural [9][12], spectroscopic [13][17], and computational studies [18][21]. Hypotheses regarding the molecular determinants of the accessibility switches have implicated the retinal/SB configuration [9], [16], [18][20], [22], changes in protein structure [13], [14], [23], [24], or a combination of multiple factors including water molecules [15], [25][29] as contributors to the switch function.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent time-resolved experiments 3,8-13 observed a photoisomerization time of ∼100-200 fs for rhodopsin and bR, which is in the range of the theoretical prediction. Several simulation studies of the photoisomerization process in rhodopsin and bR were reported 1,[14][15][16][17][18][19] since the early work of ref 6. However, these instructive studies left major questions open. The studies of Birge and co-workers 14,15,20 used basically a onedimensional model, assuming the rate of the vibrational relaxation rather than calculating it (see section III).…”
Section: Introductionmentioning
confidence: 99%